2002
DOI: 10.1046/j.1462-2920.2002.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple influences of nitrate on uranium solubility during bioremediation of uranium‐contaminated subsurface sediments

Abstract: Microbiological reduction of soluble U(VI) to insoluble U(IV) has been proposed as a remediation strategy for uranium-contaminated groundwater. Nitrate is a common co-contaminant with uranium. Nitrate inhibited U(VI) reduction in acetate-amended aquifer sediments collected from a uranium-contaminated site in New Mexico. Once nitrate was depleted, both U(VI) and Fe(III) were reduced concurrently. When nitrate was added to sediments in which U(VI) had been reduced, U(VI) reappeared in solution. Parallel studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
232
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(252 citation statements)
references
References 25 publications
(30 reference statements)
14
232
1
Order By: Relevance
“…Both factors could accelerate oxidative dissolution rather than retard it, making the observed stability of Mnreacted uraninite all the more remarkable. The conclusion that Mn-reacted uraninite is less soluble and more resistant to dissolution than unreacted uraninite is consistent with the reported increase in stability conferred by impurities to geological uraninites [8,10,11]. A recent study of the effect of Ca 2+ on biogenic uraninite has shown that contrary to Mn 2+ , this cation does not affect the kinetics of uraninite oxidation (25).…”
Section: Figure 1 U L Iii -Edge Spectra For Abiotic and Naoh-treatedsupporting
confidence: 82%
See 1 more Smart Citation
“…Both factors could accelerate oxidative dissolution rather than retard it, making the observed stability of Mnreacted uraninite all the more remarkable. The conclusion that Mn-reacted uraninite is less soluble and more resistant to dissolution than unreacted uraninite is consistent with the reported increase in stability conferred by impurities to geological uraninites [8,10,11]. A recent study of the effect of Ca 2+ on biogenic uraninite has shown that contrary to Mn 2+ , this cation does not affect the kinetics of uraninite oxidation (25).…”
Section: Figure 1 U L Iii -Edge Spectra For Abiotic and Naoh-treatedsupporting
confidence: 82%
“…A significant issue associated with uranium bioremediation is the susceptibility of biogenic uraninite, the product of microbial U(VI) reduction (2), to chemical oxidation by O 2 (3)(4)(5), nitrite (6), nitrate (4), and Fe(III) (hydr)oxides (7) and to biological oxidation coupled with nitrate reduction (8).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate inhibition of metal-reducing microbial populations, such as the SRB, hinders bioremediation efforts exploiting these microbial biocatalysts (Abdelouas et al, 1998;Finneran et al, 2002;Istok et al, 2004;Nyman et al, 2006). However, the persistence of sulfate-reducing bacteria at contaminated sites with high nitrate levels suggested the presence of potential resistance mechanisms (Gu et al, 2005;Bagwell et al, 2006;Fields et al, 2006), which were explored in this study using physiological and genomics approaches.…”
Section: Discussionmentioning
confidence: 92%
“…Evidence from both field and laboratory studies also suggest a nexus between iron redox cycling and uranium redox processes (Galloway, 1978;Posey-Dowty et al, 1987). The biostimulation of DMRB will likely lead to biological Fe(III) reduction (Wielinga et al, 2000;Finneran et al, 2002;Anderson et al, 2003;Elias et al, 2004;) and production of sorbed Fe(II) or Fe(II)-bearing minerals as metabolic products. The Fe(II)-bearing phases found include magnetite, siderite, vivianite, ferruginous smectite, and green rust (Bell et al, 1987;Roden and Zachara, 1996;Fredrickson et al, 1998;Zachara et al, 1998;Dong et al, 2000;Roh et al, 2003;O'Loughlin et al, 2007;Komlos et al, 2008;O'Loughlin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%